High-performance liquid chromatography-atmospheric pressure chemical ionization mass spectrometry and gas chromatography-flame ionization detection characterization of Delta5-polyenoic fatty acids in triacylglycerols from conifer seed oils - Lísa, Miroslav; Holcapek, Michal; Rezanka, Tomás; Kabátová, Nadezda (Journal of chromatography. A, 2007)
Edible conifer seeds can serve as a source of triacylglycerols (TGs) with unusual Delta5 unsaturated polymethylene interrupted fatty acids (UPIFAs), such as cis-5,9-octadecadienoic (taxoleic), cis-5,9,12-octadecatrienoic (pinolenic), cis-5,11-eicosadienoic (keteleeronic) and cis-5,11,14-eicosatrienoic acids (sciadonic). Conifer seed oils from European Larch (Larix decidua), Norway Spruce (Picea abies) and European Silver Fir (Abies alba) have been analyzed by non-aqueous reversed-phase high-performance liquid chromatography (NARP-HPLC) with atmospheric pressure chemical ionisation (APCI)-MS detection. The influence of different positions of double bonds in Delta5-UPIFAs on the retention and fragmentation behavior is described and used for the successful identification of TGs in each oil. TGs containing Delta5-UPIFAs have a higher retention in comparison with common TGs found in plant oils with single methylene interrupted Delta6(9)-FAs and also significantly changed relative abundances of fragment ions in APCI mass spectra. Results obtained from HPLC/MS analyses are supported by validated GC/FID analyses of fatty acid methyl esters after the transesterification. The total content of Delta5-UPIFAs is about 32% for European Larch, 27% for Norway Spruce and 20% for European Silver Fir. In total, 20 FAs with acyl chain lengths from 16 to 24 carbon atoms and from 0 to 3 double bonds have been identified in 64 triacylglycerols from 3 conifer seed oils.
Keywords: modřín; Reproducibility of Results; oleje rostlin; Plant Oils; reprodukovatelnost výsledků; terminologie jako téma; vysokoúčinná kapalinová chromatografie; Spectrometry, Mass, Electrospray Ionization; Terminology as Topic; Triglycerides; Fatty Acids, Unsaturated; semena rostlinná; atmosférický tlak; Larix; chromatografie plynová; Chromatography, High Pressure Liquid; plamínková ionizace; nenasycené mastné kyseliny; Atmospheric Pressure; Chromatography, Gas; hmotnostní spektrometrie s elektrosprejovou ionizací; Flame Ionization; triglyceridy; Seeds